The design of presumptive tax regimes in selected countries - Mas-Montserrat, Mariona (OECD Publishing, 2024)
Presumptive tax regimes (also known as simplified tax regimes) intend to reduce tax compliance costs for micro and small businesses (and enforcement costs for the tax administration) while levying a lower tax burden as compared to the standard tax system. This working paper compiles detailed information on the presumptive tax regimes existing in a selection of OECD and non-OECD countries, identifies common practices adopted across the countries examined and provides multiple examples of best practices observed in these regimes. These examples can serve as guidance to policy makers and tax administrations to strengthen particular features of the presumptive tax regimes implemented in their jurisdictions. Lastly, the paper highlights the main challenges generally observed in the presumptive tax regimes under study, which might undermine the role of these regimes in incentivising business formalisation and strengthening tax compliance over time
Keywords: Taxation; Argentina; Brazil; Colombia; Costa Rica; France; Hungary; Italy; Mexico; South Africa; Tunisia; Uruguay